Overseas immigration of fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae), invading Korea and Japan in 2019 - Wu, Ming‐Fei; Qi, Guo‐Jun; Chen, Hui; Ma, Jian; Liu, Jie; Jiang, Yu‐Ying; Lee, Gwan‐Seok; Otuka, Akira; Hu, Gao (Insect science, 2022)
The fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith), spread rapidly in Africa and Asia recently, causing huge economic losses in crop production. Fall armyworm caterpillars were first detected in South Korea and Japan in June 2019. Here, the migration timing and path for FAW into the countries were estimated by a trajectory simulation approach implementing the insect's flight behavior. The result showed that FAWs found in both South Korea and Japan were estimated to have come from eastern China by crossing the Yellow Sea or the East China Sea in 10–36 h in three series of migrations. In the first series, FAW moths that arrived on Jeju Island during 22–24 May were estimated to be from Zhejiang, Anhui and Fujian Provinces after 1–2 nights’ flights. In the second series, it was estimated that FAW moths landed in southern Korea and Kyushu region of Japan simultaneously or successively during 5–9 June, and these moths mostly came from Guangdong and Fujian Provinces. The FAW moths in the third series were estimated to have immigrated from Taiwan Province onto Okinawa Islands during 19–24 June. During these migrations, southwesterly low‐level jets extending from eastern China to southern Korea and/or Japan were observed in the northwestern periphery of the western Pacific Subtropical High. These results, for the first time, suggested that the overseas FAW immigrants invading Korea and Japan came from eastern and southern China. This study is helpful for future monitoring, early warning and the source control of this pest in the two countries. Fall armyworm (FAW) would take a round‐trip migratory cycle in eastern Asia, where they will pose a serious threat to food security. Therefore, it is very important to understand the migration path and the source area for monitoring and controlling this pest. This study, for the first time, suggested that the overseas FAW immigrants invading Korea and Japan came from eastern and southern China. This study is helpful for future monitoring, early warning and the source control of this pest in the two countries.